Not here to stay - Nur Fatin Afrina (WhiteCoat Group Sdn Bhd, 2022)
Sarah Amani is a Worldsmith. At eighteen, she accidentally conjured a mythical world she called Lagenda from her mind with the help of a past lover, Malik. Five years had passed and she was on a straight path to healing and moving on. She made sure nobody could enter Lagenda again and only allowed people to come in as wanderers by giving them petals as tickets. It was her way of ensuring that Lagenda remained hers without destroying it. Just when she thought she could leave her past, she was invited back into the world with a note saying "You know what to do. -M". She had to go back to Lagenda to make sure the person who sent her the note could not take the world from her. What Amani found is that Lagenda was not as abandoned as she thought it was. Determined to save her world from being exploited and smeared more than how it already is, she sets to burn every door and relic holding the world together. If she cannot keep Lagenda, nobody should. But it seemed that the person who sent her the note had other plans. Together with her trusty dagger, Misya, her sister, a stubborn historian called Najmi and all the misfits she never dreamed of collaborating with, she would find herself propelling straight to her dark past and beloved world.